The Impact of E-Passport Adoption on Public Trust and Immigration Management Systems in Indonesia - Gunawan Ari Nursanto; Rasona Sunara Akbar; Besse Hartati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study examines the trends in passport issuance in Indonesia for the year 2024, focusing on the transition from traditional non-e-passports to e-passports. The research aims to analyze the impact of e-passport adoption on immigration management and public service delivery. Given the increasing demand for digital transformation in public services, understanding the role of e-passports in improving service efficiency and enhancing public trust is critical. The study utilizes empirical data, including monthly passport issuance statistics from January to October 2024, comprising both e-passport and non-e-passport categories. By employing descriptive and trend analysis, the study identifies shifts in passport issuance patterns and evaluates the factors contributing to the rise in e-passport adoption. Key findings suggest a clear increase in e-passport issuance, highlighting its growing popularity and the positive effects on service efficiency, such as faster processing times and reduced administrative burdens. The study discusses the implications of e-passports on public trust in the Indonesian immigration system, suggesting that the digital shift has led to improved perceptions of service reliability and transparency.